Manufacturing challenges in the Ninth Malaysia Plan - Zubaidah, Ismail, Dr.; Siti Zawiah, Md. Dawal; Ramlee, Karim, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/